Cash Waqf Linked Sukuk (CWLS) In Indonesia: A Sentiment Analysis - Aam Slamet Rusydiana; Annisa Kartika Ocktavia; Siti Salmah (Tamkin Journal, 2023)
Currently, the government has made a new innovation in the world of waqf, namely Cash Waqf Linked Sukuk (CWLS) which is a form of social investment by collecting funds through cash waqf, then invested in state sukuk. The purpose of this research is to see the extent of development and sentiment towards Cash Waqf Linked Sukuk (CWLS). The method used is descriptive statistical analysis combined with meta and sentiment analysis of secondary data in the form of metadata from 53 Dimension indexed articles, then processed using Microsoft Excel 2019 and SentiStrenght software. The analysis shows that the topic of Cash Waqf Linked Sukuk (CWLS) has a neutral sentiment of 39.7% followed by a positive sentiment of 37.7% and a negative sentiment of 22.6%. In addition, factors that influence positive and negative sentiments towards Cash Waqf Linked Sukuk (CWLS) were also found. It can be concluded that CWLS can be a solution in increasing economic growth amid the Covid19 pandemic and economic recovery. From the results of this analysis, both positive and negative sentiments are challenges and opportunities for interested parties, including the government, academics and other stakeholders to provide a strong understanding of Cash Waqf Linked Sukuk (CWLS).